2023
DOI: 10.1039/d3bm01091k
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional calcium polyphenol networks reverse the hostile microenvironment of trauma for preventing postoperative peritoneal adhesions

Pei Zhang,
Yan Gong,
Qingqing Pan
et al.

Abstract: Abdominal adhesions, a common complication of abdominal surgery, have a high incidence and adversely affect the physical and mental health of patients. The primary causes of abdominal adhesions are intraoperative...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The underlying mechanisms driving postoperative adhesion formation are complex. The inevitable tissue damage, bleeding, hypoxia, and the local inflammatory response following surgery are of prime importance in the development of pathologic adhesion. , Hypoxia can trigger a series of intracellular responses that involve hypoxia-inducible factors, lactate, reactive oxygen species (ROS), and reactive nitrogen species (RNS), and the increased ROS/RNS level and the suppression of the antioxidant system promote the adhesion formation via oxidative stress . Meanwhile, the imbalance between these systems not only induces a deteriorating inflammatory response but also hinders the regeneration of tissue .…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms driving postoperative adhesion formation are complex. The inevitable tissue damage, bleeding, hypoxia, and the local inflammatory response following surgery are of prime importance in the development of pathologic adhesion. , Hypoxia can trigger a series of intracellular responses that involve hypoxia-inducible factors, lactate, reactive oxygen species (ROS), and reactive nitrogen species (RNS), and the increased ROS/RNS level and the suppression of the antioxidant system promote the adhesion formation via oxidative stress . Meanwhile, the imbalance between these systems not only induces a deteriorating inflammatory response but also hinders the regeneration of tissue .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the usual approach to address this challenge involves local steroid injections under bronchoscopy; however, this often fails to yield the expected results. Among the current anti-inflammatory agents, our previous research has found that polyphenolic compounds exhibit strong effects in suppressing inflammatory factors and promoting macrophage phenotype polarization [ [14] , [15] , [16] , [17] ]. Through screening potential candidate molecules, resveratrol emerged as the most promising agent for its anti-fibrotic properties and its ability to promote tissue repair.…”
Section: Introductionmentioning
confidence: 99%